2020
DOI: 10.1136/bmjopen-2020-040541
|View full text |Cite
|
Sign up to set email alerts
|

Promotion or education: a content analysis of industry-authored oral health educational materials targeted at acute care nurses

Abstract: ObjectivesTo assess the nature, quality and independence of scientific evidence provided in support of claims in industry-authored educational materials in oral health.DesignA content analysis of educational materials authored by the four major multinational oral health product manufacturers.SettingAcute care settings.Participants68 documents focused on oral health or oral care, targeted at acute care clinicians and identified as ‘educational’ on companies’ international websites.Main outcome measuresData were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Three researchers (AS, MS and QG) then constructed a semistructured data extraction instrument (online supplemental file 2) based on congruent approaches to critical analysis of policies, media and industry-authored educational materials 21 22 31. This instrument was first piloted by three researchers (MS, AS and QG) with three documents from the primary archive.…”
Section: Methodsmentioning
confidence: 99%
“…Three researchers (AS, MS and QG) then constructed a semistructured data extraction instrument (online supplemental file 2) based on congruent approaches to critical analysis of policies, media and industry-authored educational materials 21 22 31. This instrument was first piloted by three researchers (MS, AS and QG) with three documents from the primary archive.…”
Section: Methodsmentioning
confidence: 99%
“…Othman et al [ 68 ] concluded that the low quality of pharmaceutical advertisements is a global issue. Since these observations were published in 2009, there is still a conflict between promotion and information in the pharmaceutical industry [ 69 ]. Although most of these critical studies focus on written information in advertisements, visual information seems inaccurate and misleading as well.…”
Section: Discussionmentioning
confidence: 99%
“…However, even if industry educational materials appear “evidence based,” research suggests these materials need to be thoroughly vetted and may not be a reliable source of information. For example, in a recent study of educational materials authored by companies that manufacture oral health products, we found that most made product-related claims but that nearly half of these claims were not accompanied by any evidence (Grundy et al, 2020). Those that did provide a citation often cited scientific articles that were not related or exaggerated the benefits of the study's findings.…”
Section: Education About a Product Instead Of A Practicementioning
confidence: 99%